E.N.A.P 2017-2018 آليات الرقابة الداخلية كمدخل لتحسين الآداء ‬‬ في المؤسسة الاقتصادية دراسة حالة المؤسسة الوطنية للدهن - مراد ‫خلي‬‫ـ‬‫فة‬; صبحي بن نخلة (My University, 2018)
In this study, we have highlighted the role of internal control to improve the performance of economic enterprises and understanding the concept of internal control and of its components, as well as the procedures followed for its application and its contribution to improving economic performance. In our field study, we used the statistical analysis of hypothesis testing in interpreting a sample composed of a group of accountants and observers at the institute national fat, in order to determine the contribution of internal control to the improvement of economic business performance. The study concluded that the implementation of the internal control system contributes to the achievement of business objectives. Which is to achieve maximum profit, which puts into .............................................................. وقد سلطنا في هذه الدراسة الضوء على دور الرقابة الداخلية في تحسين أداء الشركة أداء المؤسسات الاقتصادية وفهم مفهوم الرقابة الداخلية و مكوناته والإجراءات المتبعة لتطبيقه والمساهمة فيه تحسين الأداء الاقتصادي. استخدمنا في دراستنا الميدانية التحليل الإحصائي لاختبار الفرضيات في تفسير عينة مكونة من مجموعة من المحاسبين والمراقبين في المعهد الدهون الوطنية، وذلك لتحديد مدى مساهمة الرقابة الداخلية في تحسين أداء الأعمال الاقتصادية. وتوصلت الدراسة إلى أن تطبيق نظام الرقابة الداخلية يساهم في تحقيق النتائج المرجوة تحقيق أهداف العمل. وهو تحقيق أقصى قدر من الربح، وهو ما يضع في يدل على المستوى الجيد في الشركة.